Integrated Aeroponic Technology for Enhancing Community-Based Potato Seed Production in North Sumatra - Diningrat, Diky Setya; Harahap, Novita Sari; Prima, Heppy Setya; Febriyossa, Adelia; Maulana, Bagoes; Sibuea, Abdul Muin; Sari, Laela; Jamaludin, Askiah Binti (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: Indonesia’s potato production faces critical challenges in quality seed provision. Traditional G0 seed propagation methods achieve only 40-60% survival rates due to transplant shock and environmental stress. Contribution: This research contributes to community-based technology transfer literature in agricultural seed systems by implementing integrated aeroponic-micro tuber technologies through participatory partnerships. Method: A participatory action research approach was employed over four months (January-April 2025) involving 25 participants from Gapoktan Nilam farmer group in North Sumatra. The tri-partite partnership included farmers, PT. G10 Agrotech, and Universitas Negeri Medan. Training modules covered aeroponic fundamentals, micro-tuber applications, and integrated system management. post assessments measured survival rates, productivity, knowledge, and skills using paired t-tests. Results: Survival rates improved significantly from 52.3±8.2% to 83.7±4.1% (p<0.001). Monthly seedling production increased by 171% from 2,040±320 to 5,520±280 units. Participant knowledge scores doubled from 4.2±0.8 to 8.5±0.6 (p<0.001). The program achieved 95% participation with 78% satisfaction rates and demonstrated 240% return on investment within 12 months. Conclusion: The integrated approach effectively addresses transplant shock while establishing sustainable community partnerships. This model demonstrates successful scaling of complex agricultural technologies at grassroots level, contributing to enhanced food security through improved seed systems.